Bacteriophage Therapy for Treating Infections: Hope or Hype? - Nasa, Anurag (Trinity Student Medical Journal, 2022)
Bacteriophage therapy employs the use of viruses to kill bacteria and has been noted to confer reversal of antimicrobial resistance. It was proposed around the same time as antibiotic therapy for combatting infections but lost the race for becoming the mainstay therapy. However, antibiotic resistance is increasingly resulting in morbidity and mortality. Bacteriophage therapy as an alternative approach for combatting infections has garnered speculation and interest of many scientists with hopes that it may become a management strategy for multi-drug resistant infections. The aim of this review is to shed light on the developments in bacteriophage therapy, explain lytic cycles as the proposed functional mechanism and discuss the evidence base: preclinical, case-based and clinical trials. There is preliminary evidence that alludes to an element of safety and efficacy in treating multidrug resistant infections. However, there is a paucity of high-quality evidence, which could bring this therapy into routine practice. This is further burdened by limitations such as the need for an individualised approach and our lack of understanding of the immune reactions to it. This therapy is quite promising, but much work is needed before it can be considered for routine clinical practice.